Locally Advanced Scalp Tumors: Clinical and Survival Outcomes of a Tertiary Unit. Issue 3 (September 2021) - Sleiwah, Aseel; Mughal, Maleeha; Thomas, Nicholas; Roblin, Paul; Townley, William; Jeannon, Jean-Pierre
Abstract : Introduction: Locally advanced nonmelanoma skin cancers of the head and neck are well described in the current literature. However, data about clinical and survival outcomes are lacking. We present survival data from a tertiary head and neck cancer unit in London. Methods: A retrospective analysis of data collected from a single institution was conducted. All patients with locally advanced cutaneous scalp carcinomas invading the skull between 2011 and 2019 were included. Data included patient demographics, tumor, comorbidities, interventions, flap survival, and metal work exposure. Survival outcomes were examined using Kaplan-Meier analysis. Results: Twenty-three patients were identified. The mean age was 72 years. Eighteen patients were male, and 5 were female. Five patients were immunosuppressed. Nineteen patients underwent outer cortex drill-down/full-thickness calvarial resection, followed by reconstruction with free tissue transfer. Six patients had titanium mesh reconstruction after segmental skull resections. Three patients underwent further surgery because of exposed metalwork. Disease-free survival at 3 years after surgery was 60%. Conclusions: Locally advanced nonmelanoma skin cancers invading the bone are sporadic. There are little published data on clinical and survival outcomes in this group. Despite the nature of these skin lesions, a high degree of local control can be obtained by extensive surgical resection, outer table drill-down, and calvarial resection. We conclude that aggressive management of the bony invasion improves disease-free survival and improves local control.